Microbiological Evaluation of the Pathogens Isolated From the Endotracheal Aspirate Samples of the Patients Followed in the Intensive Care Units: A One-Year Retrospective Analysis - Sagmak-Tartar, Ayse; Ozer, Ayse Belin; Ulu, Ramazan; Akbulut, Ayhan (Doc Design Informatics Co Ltd, 2018)
Objective: The aim of this study was evaluation of distribution of microorganisms and their antimicrobial resistance rates isolated from endotracheal aspirate (ETA) samples of patients under mechanical ventilation in intensive care units (ICUs) of our hospital. Methods: ETS culture results of ICU patients were retrospectively evaluated during one-year period between January 2016 and January 2017. Bacteria isolated from cultures of ETA samples were identified by conventional methods and VITEK (R) 2 (bioMerieux, Marcy l'Etoile, France) automated system. Antimicrobial susceptibility testing results were interpreted according to the Clinical and Laboratory Standards Institute criteria. Results: In one-year period, 1470 ETA samples were accepted to the laboratory, and 620 of these samples were culture-positive. Cultures of samples yielded isolates of 307 (49.5%) Acinetobacter baumannii, 127 (20.5%) Pseudomonas aeruginosa, 101 (16.3%) Klebsiella spp, 23 (3.7%) coagulase-negative staphylococci, 13 (2.1%) Staphylococcus aureus, 23 (3.7%) Serratia marcescens, 15 (2.4%) Escherichia coli, 3 (0.5%) Enterobacter spp., 1 (0.2%) Stenotrophomonas maltophilia, 1 (0.2%) Sphingomonas sp. and 6 (1%) Candida spp. High resistance to imipenem was remarkable among Gram-negative isolates. Resistance rates to imipenem were 97.7% in A. baumannii, 78.3% in S. marcescens, and 70.9% in P. aeruginosa. Colistin-resistance rates were 2.9% in A. baumannii, 2.4% in P. aeruginosa, 5% in. K. pneumoniae, and 4.3% in S. marcescens. Methicillin resistance was 86.4% and 100% among coagulase-negative staphylococci and S. aureus, respectively. Conclusions: Regular analyses and monitorization of ventilator-associated pneumonia agents together with their antibiotic susceptibilities should be performed to direct appropriate empirical antibiotic treatment strategies in ICU. Taking into consideration the panresistant strains and increased resistance rates, strict adherence to infection control measures and appropriate infection control strategies are crucial to prevent ICU infections.
Endotrakeal aspirat örneklerinden İzole edilen bakteriler ve antibiyotik duyarlılıkları: Bir yıllık retrospektif analiz
Keywords: Endotracheal aspirate; intensive care units; anti-bacterial agents